PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA MANAJERIAL (Studi Empiris pada Perusahaan Swasta dan BUMN Cabang Kota Bengkulu) - Nadia Zulfa Rinda; Fitri - Santi; Baihaqi - - (Student Journal of Business and Management, 2021)
A company in an effort to run its business requires a structured and systematic rule in providing direction and elements within the company to maximize its performance. One such structured effort is implementing TQM. Total Quality Management (TQM) is a paradigm in running a business that seeks to maximize organizational competitiveness through a focus on customer satisfaction, involvement of all employees, and continuous improvement of the quality of products, services, people, processes and organizational environment. According to (Kujala & Ullrank, 2004) and (Metri, 2005), organizational culture is one of the most important variables in the success or failure of a TQM program. The prevailing organizational culture is believed to be able to support TQM by providing a more conducive environment that paves the way for the successful implementation of TQM (Baird et al., 2011). Managerial behavior has been observed to have an interest in the job performance of employees in organizations (Andersson & Florén, 2011; Wong & Li, 2015) indicating that manager behavior strongly influences employee and customer satisfaction in the workplace. This study examines the effect of Total Quality Management (TQM) and organizational culture on managerial performance in private companies and BUMN branches in Bengkulu city. The sample used in this study are managers who work in private companies and state-owned enterprises in Bengkulu City. The questionnaire distributed was 146 copies, which returned 137 copies, which did not return 9 copies, so the total that could be processed was 137 copies. The sampling technique in this study is purposive sampling (sampling with the aim of) that is sampling with managers of private companies and state-owned enterprises. The analytical tool used is SPSS. Based on the results of the study, total quality management has a positive effect on managerial performance, meaning that the better state and private companies in Bengkulu implement total quality management, the better managerial performance will be. Based on the results of the study, organizational culture has a positive effect on managerial performance, meaning that the better the culture in BUMN and private companies in Bengkulu, the better managerial performance. As for the limitations of this study, the obstacles during the research process were the difficulty of obtaining research permits in state-owned and private companies, because the respondents were managers, and the waiting period for the withdrawal of the questionnaire. Keywords: Total Quality Management, Organizational Culture, Managerial Performance and SPSS.